Islamic Value-Based Leadership in the Healthy Madrasah Program: A Qualitative Case Study at a Madrasah Aliyah Negeri - Mulyawan Safwandy Nugraha; Ai Rohayani (STAI Hubbulwathan Duri, 2025)
The Healthy Madrasah Program is a national initiative by Indonesia’s Ministry of Religious Affairs aimed at integrating Islamic values with school health promotion. However, limited research explores how Islamic leadership operationalizes such values into routine governance and student culture. This qualitative case study investigates the implementation of the program at MAN 1 Sukabumi, a 2024 district-level award recipient. Eighteen participants were purposively selected, including school leaders, teachers, students, parents, UKS staff, and a canteen vendor. Data were collected through semi-structured interviews, non-participant observations (12 sessions), and document analysis (RKT, SOPs, memos, and social media posts). Data were analyzed using reflexive thematic analysis, supported by a PDCA (Plan–Do–Check–Act) framework. Three themes emerged. First, value-anchored modelling: leadership exemplified Islamic values—ihsan, ta’dib, tazkiyah—through visible acts (e.g., picking up litter, value-based assemblies), normalizing clean and orderly behavior. Second, governance routines: the PDCA cycle operationalized values into measurable practices, such as handwashing click counts, class tidiness rubrics, and vendor compliance checks, enabling micro-adjustments like bin relocation and schedule tweaks. Third, distributed participation: student leaders (OSIS/MPK, PHBS ambassadors) coordinated health routines, improving lesson readiness and peer accountability. Leadership practices rooted in Islamic values, structured through PDCA, helped embed a health-supportive school culture. Key implications include codifying value-based routines in SOPs, adopting lightweight monitoring dashboards, and formalizing home–school coordination. Findings suggest value-integrated governance can enhance sustainability in school health programs.